Adding multi-material regions embracing the tip leads to significant capacity increase in structures weakened by V-notches under antiplane shear and torsion. (15th August 2022) - Salviato, Marco
Abstract: This study investigates how the insertion of multimaterial circular regions embracing the tip of a finite V-notch can be used to reduce the Notch Stress Intensity Factors (NSIFs) in structures subjected to antiplane shear or torsion. Towards this goal, this work presents a novel theoretical framework to calculate stress distributions and NSIFs in closed-form. Thanks to the new solution, it is shown that by tuning multimaterial region radii and elastic properties it is possible to significantly reduce the NSIFs and stress concentrations at the material interfaces. To investigate whether the proposed multimaterial system translates into increased structural capacity even in the presence of significant nonlinear deformations, computational simulations were conducted using nonlinear hyperelastic-damage and elasto-plastic-damage models. The preliminary results show increases of structural capacity up to 46% and of nominal strain at failure of up to 86% at the expenses of only a 8% reduction in structural stiffness. It is expected that a similar approach can be extended to other loading conditions (e.g. mode I and mode II, and fatigue) and that even larger gains can be obtained by performing thorough optimization studies. Graphical abstract: